Project-based Learning: EFL Students’ Involvement in Collaborative Writing - Rofik, Abdur (Faculty of Tarbiyah and Teacher Training, IAIN Jember, 2023)
Project Based Learning (PBL) is a student-centred learning approach in which a teacher acts as a facilitator to help a student solve a problem. In the present study, involvement is a substantial element in PBL because the student is required to learn collaboratively in a group project. Therefore, the study aims to discover how the student is involved in accomplishing scholarly writing in a group project, and what the opportunity of writing a scholarly article collaboratively is. The present research is a case study in a private university in Indonesia. The data are gained from a questionnaire and an interview. The data then are analyzed qualitatively. The study discovers that PBL is believed to activate EFL students’ involvement in terms of contributing to the team project, handling responsibility, and respecting teammates. The opportunities of PBL implementation in writing experienced by the students are getting ideas, designing the project, tunning the project, writing the project, exhibiting the project, and evaluating the project. Finally, the study is expected to provide teachers with practical ideas for implementing PBL effectively in a writing context.